How the use of the term "schizo*" has changed in an Italian newspaper from 2001 to 2015: Findings from a descriptive analysis. (December 2018) - Pingani, Luca; Sampogna, Gaia; Borghi, Giulia; Nasi, Annamaria; Coriani, Sandra; Luciano, Mario; Galeazzi, Gian Maria; Evans-Lacko, Sara; Fiorillo, Andrea
Highlights: Majority of articles containing the term "schizo" are not related to mental health. The number of articles containing the term "schizo constantly decreased from the year 2001 to 2015. Information in articles about help-seeking and referral to mental health services are lacking. The percentage of articles that did not respect the privacy of people with a mental disorder is very high. Abstract: The study aims to report the number of newspaper articles including the word "schizo" in the period 2001 – 2015 and to identify possible predictors reinforcing negative stereotypes about people with schizophrenia. The electronic archives of the Italian newspaper "La Stampa" have been searched for the term "schizo". Selected articles were grouped in articles related to mental health (rMH) or article not related to mental health (nrMH). 946 articles were identified. Schizophrenia-related terms were used in 356 (36.03%) article rMH, which mainly reinforce negative stereotypes regarding mental illness both in rMH and nrMH groups. Over time, only in the rMH group a significant reduction of articles reinforcing negative stereotypes was found. Several factors have been identified as predictors of article reinforcing negative stereotypes: unnecessarily dramatic or sensational headline or content; inaccurate or not in the correct context use of medical terminology; emphasis to the illness rather than to the person; mental disorders are the same; disclosure of particular individual has a mental illness. Although there has been a significant reduction in stigmatizing articles, in the rMH group one article out of three reinforces negative stereotypes.